The impact of financial constraints on the convertible bond announcement returns - Chong-Chuo Chang; Tai-Yung Kam; Chih-Chung Chien; Wan Ting Su (Economies, 2019)
As of now, very few research studies have examined the effects of financial constraints on the short- and long-term performances of companies after their announcement of convertible bonds. Due to asymmetric information, previous studies consider issuance of convertible bonds as negative news. As a result, the short- and long-term performances of companies generally decline after their convertible bond announcement. This study argues that when companies have investment plans, they are expected to have higher future cash flows. They will become increasingly more valuable regardless of the fact that they raise funds through the issue of convertible bonds (due to financial constraints), positively affecting the performance of companies. The results indicate that financial constraints have no effect on short-term performance, but did have a significantly positive impact on the long-term performance of companies after their issuance of convertible bonds.
Keywords: 330; convertible bond; financial constraints; stock performance